Multidetector CT cystography for imaging colovesical fistulas and iatrogenic bladder leaks - Tonolini, Massimo (Springer-Verlag, 2012)
Multidetector computed tomography (MDCT) cystography currently represents the modality of choice to image the urinary bladder in traumatized patients. In this review we present our experience with MDCT cystography applications outside the trauma setting, particularly for diagnosing bladder fistulas and leaks. A detailed explanation is provided concerning exam preparation, acquisition technique, image reconstruction and interpretation. Colovesical fistulas most commonly occur as a complication of sigmoid diverticular disease, and often remain occult after extensive diagnostic work-up including cystoscopy and contrast-enhanced CT. We consistently achieved accurate preoperative visualization of colovesical fistulas using MDCT cystography. Urinary leaks and injuries represent a non-negligible occurrence after pelvic surgery, particularly obstetric and gynaecological procedures: in our experience MDCT cystography is useful to investigate iatrogenic bladder leaks or fistulas. In our opinion, MDCT cystography should be recommended as the first line modality for direct visualization or otherwise confident exclusion of both spontaneous enterovesical fistulas and bladder injuries following instrumentation procedures, obstetric or surgical interventions. Main Messages • Explanation of exam preparation, acquisition technique, image reconstruction and interpretation. • Preoperative visualization of colovesical fistulas, usually secondary to sigmoid diverticulitis. • Visualization or exclusion of iatrogenic bladder injuries following instrumentation or surgery.